Teratogenic effects of the oral titanium dioxide NP(Tio2) on morphology and skeletal structure of fetal mice NMRI in different gestational weeks - Mohamad Hasan Abdi Ardestani; Morteza Anvari; Abbas Shahedi; Maryam Yadegari; Arezoo Khoradmehr; Sedigheh Rastaghi (Mashhad University of Medical Sciences, 2018)
Introduction: Considering the development of nanotechnology and extensive use of nano-materials are in different fields of industry, it is necessary to investigate their destructive effects on biological systems. Titanium dioxide (TiO2) is used in the production of different dyes, cosmetics, ceramics, photocatalysts, water and sewage treatment and a lot of other products. This study was performed with aim to evaluate the Teratogenic effect of TiO2 in different gestational weeks of NMRI mice. Methods: This experimental study was performed on 30 female NMRI mice (25-30 gr, 8-12 weeks of pregnancy) in 2017. The mice were randomly assigned into 2 control groups and 4 case groups). Pregnancy was confirmed with vaginal plaque (GD0). The doses of 5 mg/kg of tio2 solution were orally gavage to pregnant mice from the first to 18th days of pregnancy. The first group, the first week of pregnancy, the second group, the second week of pregnancy and the third group received nanoparticles only in the third week of pregnancy and the fourth case group were treated during all period of pregnancy. The Sham group was gavage with solvent and control group received city water without gavage. In the 18th day of pregnancy, the fetuses were removed from the uterine tubes and their weight and height, Head circumference and morphologic disorders were recorded, their skeletal disorders were checked by alizarin red and painting. Data were analyzed by SPSS software (version 21). P<0.05 was considered significant. Results: Totally, significant reduction in body weight and CR length was observed in all four experimental groups in comparison with control group (P<0.05). Also, significant increasing was observed in appearance abnormalities such as fetal absorption, bleeding, organs abnormalities, and skeletal disorders in experimental groups in comparison with control group. The observations showed more incidence of Teratogenic effect in the group which was exposed to nanoparticles in second week. Conclusion: The results of present study prove the toxicity and teratogenicity effects of TiO2 nanoparticles on living organisms. So, further studies are recommended to predict the toxicity effect of TiO2.